2015
DOI: 10.1007/s11947-015-1561-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antioxidant Capacity, and Sensory Quality of Dried Sour Cherry Fruits pre-Dehydrated in Fruit Concentrates

Abstract: The aim of this study was to determine the effect of combined drying methods by osmotic dehydration (OD) using several fruit concentrates (apple, blackcurrant, chokeberry, sour cherry, raspberry, quince, flowering quince) or sucrose solution, before combined drying involving convective drying (CD) and vacuum-microwave finish drying (VMFD), on the quality parameters (phenolic compounds, antioxidant activity, color, and other chemical parameters (titratable acidity, pH, dry matter, and water activity)) of dried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 50 publications
(81 reference statements)
6
27
0
1
Order By: Relevance
“…The increase in polyphenolic compounds was related to the penetration of solids from the osmotic solution to the dehydrated material. Similar results were observed during the dehydration of beetroots [25] and cherries [4] in concentrated chokeberry juice. Even greater increase in PC was obtained for pumpkin dehydrated in concentrated flowering quince juice.…”
Section: Values Of Determination Coefficientsupporting
confidence: 84%
See 3 more Smart Citations
“…The increase in polyphenolic compounds was related to the penetration of solids from the osmotic solution to the dehydrated material. Similar results were observed during the dehydration of beetroots [25] and cherries [4] in concentrated chokeberry juice. Even greater increase in PC was obtained for pumpkin dehydrated in concentrated flowering quince juice.…”
Section: Values Of Determination Coefficientsupporting
confidence: 84%
“…In the case of pumpkin samples dehydrated in raspberry juice, the increase was only over 2 times. Similar results were obtained for cherries dehydrated in concentrated flowering quince and raspberry juices [4]. It can be concluded that the dehydration in osmotic solutions improves the quality of the final products in terms of the content of biologically active components [41].…”
Section: Values Of Determination Coefficientsupporting
confidence: 77%
See 2 more Smart Citations
“…Thus, the use of sweeter and less acidic fruits, as well as the reconstitution matrix, influences the sweetness intensity of the smoothies. Indeed, other studies (Nowicka et al ., , ) showed that sweeter products were characterised with higher ratings to the degree of liking by consumers while the more acidic ones were less accepted. The results found in the present work are quite interesting, because even with the low degree of liking obtained using a hedonic scale (Table ), smoothies with milk presented appreciable percentages of ideal intensity of sweetness, showing that some consumers will accept lower sugar content, which is in line with the need to reduce Brazilian sugar consumption (Brasil, ).…”
Section: Resultsmentioning
confidence: 99%